PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS GAME PUZZLE PADA MATERI MICROSOFT WORD KELAS X BD 2 SMK PGRI 1 TULUNGAGUNG - TIRO ASMARA QONDY, MOCHAMAD; DWI PAMUNGKAS, BIAN; PANGGAYUH, VERTIKA (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The predominance of PowerPoint in Informatics learning at SMK PGRI 1 Tulungagung created a mainly one way learning process and limited students' active engagement. This study aimed to develop puzzle game based learning media for Microsoft Word in Class X BD 2 and determine its feasibility. The study employed Research and Development using the ADDIE model, which consists of Analyze, Design, Develop, Implement, and Evaluate. The needs analysis involved classroom observation, teacher interviews, student characteristics, learning devices, and the scope of Microsoft Word material. The product was developed with Construct 2, supported by visual assets from Canva, and distributed in HTML5 format for Android devices. The media contains instructions, learning objectives, structured material, puzzle activities, quizzes, direct feedback, and simple rewards. Data were collected through observation, interviews, and questionnaires involving one media expert, one subject matter expert, seven students in a small group trial, and 31 students in a large group trial. Media expert validation increased from 74.11% before revision to 96.43% after revision. Subject matter validation increased from 90.91% to 97.73%. The small group trial achieved 83.93%, while the large group trial achieved 84.88%. These findings indicate that the developed media is highly valid and highly feasible as a supporting medium for Microsoft Word instruction. The product can help teachers present material more interactively and provide students with a more active, attractive, and enjoyable learning experience. Keywords: ADDIE, learning media, Microsoft Word, puzzle game, research and development